Detection of Extended-Spectrum β‑Lactamase-Producing Escherichia coli Using Infrared Microscopy and Machine-Learning Algorithms - Sharaha, Uraib; Rodriguez-Diaz, Eladio; Sagi, Orli; Riesenberg, Klaris; Lapidot, Itshak; Segal, Yoram; Bigio, Irving J; Huleihel, Mahmoud; Salman, Ahmad (Analytical chemistry (Washington), 2019)
The spread of multidrug resistant bacteria has become a global concern. One of the most important and emergent classes of multidrug-resistant bacteria is extended-spectrum β-lactamase-producing bacteria (ESBL-positive = ESBL+). Due to widespread and continuous evolution of ESBL-producing bacteria, they become increasingly resistant to many of the commonly used antibiotics, leading to an increase in the mortality associated with resulting infections. Timely detection of ESBL-producing bacteria and rapid determination of their susceptibility to appropriate antibiotics can reduce the spread of these bacteria and the consequent complications. Routine methods used for the detection of ESBL-producing bacteria are time-consuming, requiring at least 48 h to obtain results. In this study, we evaluated the potential of infrared spectroscopic microscopy, combined with multivariate analysis for rapid detection of ESBL-producing Escherichia coli (E. coli) isolated from urinary-tract infection (UTI) samples. Our measurements were conducted on 837 samples of uropathogenic E. coli (UPEC), including 268 ESBL+ and 569 ESBL-negative (ESBL–) samples. All samples were obtained from bacterial colonies after 24 h culture (first culture) from midstream patients’ urine. Our results revealed that it is possible to detect ESBL-producing bacteria, with a 97% success rate, 99% sensitivity, and 94% specificity for the tested samples, in a time span of few minutes following the first culture.